2014
DOI: 10.1227/neu.0000000000000117
|View full text |Cite
|
Sign up to set email alerts
|

5-Aminolevulinic Acid-Induced Protoporphyrin IX Fluorescence in Meningioma

Abstract: BACKGROUND The use of 5-aminolevulinic acid (ALA)-induced protoporphyrin IX (PpIX) fluorescence has shown promise as a surgical adjunct for maximizing the extent of surgical resection in gliomas. To date, the clinical utility of 5-ALA in meningiomas is not fully understood, with most descriptive studies using qualitative approaches to 5-ALA-PpIX. OBJECTIVE To assess the diagnostic performance of 5-ALA-PpIX fluorescence during surgical resection of meningioma. METHODS ALA was administered to 15 patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
84
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(92 citation statements)
references
References 58 publications
(95 reference statements)
3
84
0
3
Order By: Relevance
“…A recent study of 15 patients reported 5-ALA positivity for 80% of meningioma cases. 43 The overall high rate of 5-ALA positivity suggests that 5-ALA could be a useful surgical adjunct, especially in the presence of ill-defined tumor margins (bone, dura, and brain parenchyma invasion), which is seen with some high-grade meningiomas. 26 …”
Section: -Ala Fluorescence In Meningiomasmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study of 15 patients reported 5-ALA positivity for 80% of meningioma cases. 43 The overall high rate of 5-ALA positivity suggests that 5-ALA could be a useful surgical adjunct, especially in the presence of ill-defined tumor margins (bone, dura, and brain parenchyma invasion), which is seen with some high-grade meningiomas. 26 …”
Section: -Ala Fluorescence In Meningiomasmentioning
confidence: 99%
“…5,43,45 More recently, a retrospective study of 52 patients demonstrated that 62% of brain metastases were positive for intraoperative 5-ALA fluorescence. 20 Preliminary reports indicate that 5-ALA fluorescence increases the safety and accuracy of stereotactic and endoscopic brain biopsy procedures.…”
mentioning
confidence: 99%
“…Therefore, spectroscopic probes for quantitative assessment of PpIX fluorescence were introduced for neurosurgical procedures. 8,40,41 With the use of such spectroscopic probes, small residual fluorescing foci can be more objectively identified. Furthermore, small amounts of PpIX accumulation were detected even in macroscopically nonfluorescing tumors.…”
Section: Future Directionsmentioning
confidence: 99%
“…At the same time, no statistically significant effect on the overall survival rate was identified. Nevertheless, this technology has attracted an increased attention of neurosurgeons resulting in more reports on FN, as well as the application of this method for other central nervous system tumors [4,[7][8][9][10][11][12][13][14][15][16] including intracranial meningiomas [16][17][18][19][20]. However, the assessment of FN's sensitivity and specificity was not demonstrated clearly and in particular, no comparison was made between the data obtained from visible fluorescence, and the data obtained from laser biospectroscopy in meningiomas of different World Health Organization (WHO) grades.…”
Section: Introductionmentioning
confidence: 99%